How to maintain the effective levels of probiotics throughout the shelf life in yoghurt: A review - Vargáné Visi, Éva; Pápai, Gréta (Acta Agraria Kaposváriensis, 2015)
Retention of probiotic functionality throughout the entire shelf life of probiotic yoghurt can be a challenge for manufacturers. The review was aimed to interpret the factors that have an influence on the growth of probiotic microorganisms in fermented dairy foods, especially in yoghurts. Compatibility between strains is important both for the manufacture and storage of the product. Inoculation with commercial and probiotic cultures results in complex interaction among strains that is advisable to consider during strain selection and setting of fermentation conditions. Processing steps like cold ripening and storage of yoghurt can represent a threat for the viability of probiotic bacteria as an adverse environment is present. The most important factors that can be a matter of concern are the presence of oxygen, low pH and cold stress. Strategies to eliminate the drawback of these conditions based on chemical and enzymatic methods and technological developments with respect to packaging. Growth is strongly influenced by ingredients involved into the food matrix. Incorporation of prebiotics can improve the viability of probiotics during manufacturing and storage of yoghurt and can contribute to the achievement and maintenance of effective cell numbers to confer beneficial effects for the host. The prerequisite of the effective use of prebiotics is their chemical stability under the applied manufacturing conditions.
Keywords: probiotic viability; bifidobacteria; prebiotics; inulin; yoghurt storage